Geochemical characterization of the Equatorial Atlantic Magmatic Province and its correlation with other magmatic events related to the South Atlantic Opening - Macêdo Filho, Antomat Avelino de (2021)
Tholeiitic magmatism, Magmatic plumbing systems, EM component, West Gondwana breakup, Large Igneous Provinces (Angola). These aspects combined with the possible physical link between the Rio Ceará Mirim and Transminas (PEMP) swarm and Riacho do Cordeiro and Vitória-Colatina swarms (PEMP) indicate that both provinces share similar mantle sources and magmatic processes. Consequently, it can be assumed that EQUAMP and PEMP form together a continental scale tholeiitic event related to the early opening stage of the South Atlantic Ocean, therefore designed as one major single LIP of Lower Cretaceous age that should be collectively referred as the South Atlantic Magmatic Province (SAMP).